Striking a balance: Designing a blockchain-based solution to navigate coopetition dynamics in supply chain management - Jonathan Lautenschlager; Jan Stramm; Tobias Guggenberger; Nils Urbach (Electronic Markets, 2025)
Coopetition dynamics, which refer to the simultaneous competition and cooperation, increasingly affect the management of digital supply chains. Current research profoundly explores the benefits and drawbacks of using blockchain systems in coopetition strategies to boost cooperation and automation in supply chains. However, these systems often do not adequately address how to manage competition dependencies, which practitioners need to address when considering adopting a blockchain solution that contains excessive disclosure of sensitive information during the data exchange within a transparent network. This paper examines how to protect such sensitive information essential for maintaining competitive dynamics. Following a design science research approach, we suggest a blockchain architecture specifically tailored to the construction industry. We focus on components that manage competition and privacy-enhancing technologies that address the trade-off between cooperation benefits and the need to protect sensitive business data, which is especially crucial in supply chain automation. This study contributes to the current scientific discourse by designing and deriving implementation guidelines for a solution that incorporates the benefits while addressing the potential drawbacks of blockchain technology through coopetitive data exchange to diffuse blockchain solutions into practice successfully.
Keywords: O14; 620; Coopetition; Blockchain technology; Data transparency; Delivery invoices; Construction industry; Supply chain automation